COVID-19 associated mucormycosis: a case report in Pakistan and a review of 144 cases - Zameer, Sheharyar; Syed, Ramsha; Afzal, Areesha; Amir, Raham; Faridi, Shanza; Nayyar, Afsa (Journal of the Pakistan Medical Association, 2022)
Mucormycosis is the third most common mycosis in order of its importance as a human pathogen, occurrence of which has become more frequent around the world. Although not proven as a causal association, the increased number of cases has been attributed to Covid-19, the rampant use of corticosteroids, and diabetes. We report the case of a 53-year-old male with mucormycosis related to a Covid-19 infection as the novel case from Pakistan and discuss its epidemiology, diagnostic principles, and management. In our literature review, this is the 145th case being reported with most cases occurring in India, mostly in males, of rhino-orbital form and about a third of them leading to the death of the patient. Keywords: Black Fungus, Phycomycosis, Zygomycosis, Diabetes Mellitus, Corticosteroids